Analysis Of Technical Specifications Of 180 GT Purse Seine Vessel In Fishing Line III Fisheries Management Area (FMA) 572 - Mei Edi Prayitno; Marimin; Taryono; Sugeng Hari Wisudo (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2022)
Fishing vessels for catching small pelagic fish resources in fishing line III FMA 572 are dominated by vessels with a capacity of <30 GT. The capacity of vessels and fishing gear for pelagic types is 180 GT purse vessels. The research is study development of technical specifications of 180 GT purse seine vessel. The research method is a research design of 180 GT fishing vessels with Autocad and Maksurf software. The findings of the technical specifications of purse seine vessels are 180 GT with a length of 35.30 m with a speed of 8 knots. This fishing vessel uses purse seine fishing gear with a length of 600 m and a width of 150 m, which is equipped with a power block and fish pump, which can increase crew efficiency by 40% to 46% and the time for setting net purse seine, hauling and braiiling is faster by 16, 67% to 42.86%. This 180 GT purse seine vessel can operate for 50 days with 27 crews with a fuel tank capacity of 44,525 tons. In the shipbuilding process, it is recommended to use domestic components and material products to increase the speed of the production process and ease the supply of spare parts.